Kondisi Terumbu Karang dengan Indikator Ikan Chaetodontidae di Pulau Sambangan Kepulauan Karimun Jawa, Jepara, Jawa Tengah. - Suryanti Suryanti; Supriharyono Supriharyono; Willy Indrawan (Buletin Oseanografi Marina, 2011)
Abstract Coral reefs are marine ecosystems in tropical marine life constructed by the producer of lime in particular species of stony corals and calcareous algae, together with the biota that live in the bottom of which is a types of molluscs, crustaceans, echinoderms, Polychaeta, Sponge and tunicates and marine biota others are living freely in the surrounding waters. Chaetodontidae or butterfly fish is ordinary reef fish while the distribution in surround coral reef only. The experts agreed on placing fish leadership as "indicator species" of coral reef condition, because this fish is a true coral reef inhabitants. This study aims to identify relationships between the abundance of coral reef condition Chaetodontidae fish in waters of Sambangan Islands, Karimun java, Jepara, Central Java. Research was conducted in July 2010 in waters Sambangan Island, National Park Karimunjawa. The research method is field observation method with the sampling method using the line transect method (line transect) on coral and fish transect data on fish along the 30m data. Data taken in this study are the data of physical parameters, data, coral cover and fish abundance. Results from this study showed that the percentage of coral coverage at a depth of three meters amounted to 70.92% and at a depth of 10 meters amounted to 66.05%. Closing percentage is the highest Reef on the West side of site B with a depth of three meters is equal to 82.50% while the percentage of closures of the least Reef is on the East side of site A with a depth of 10 meters that is equal to 64.80%. Types of coral reef growth that dominated in the waters of the island is Acropora Branching Sambangan. Percentage value of 16.71. The average abundance of fish on each transect Chaetodontidae with a depth of 10 meters (10 individuals / transect) is smaller than the depth of three meters (11 individuals / transect). The relationship between the abundance of fish Chaetodontidae with Closure Percentage Sambangan Coral Island at a depth of 3 meters is strong (Significant) and Positive (DC), whereas at a depth of 10 meters is a weak (non-Significant) and Positive (DC).   Keywords : percentage of coral coverage, Abundance of fish Chaetodontidae